For the love of books! campaign - Lestarini Saraswati Hapsoro (2014)
This paper presents the communication campaign For the Love of Books!, an initiative that promotes leisure reading amongst young adults in Singapore organised by four final year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Targeting young adults aged 18 to 30, this campaign aims to broaden the reading scope of these individuals by reconceptualising leisure reading as an entertaining activity and by increasing the accessibility of reading to incentivise more individuals to pick up the habit. The campaign is broken down into three key aspects, which includes a social media engagement plan, outreach efforts in tertiary institutions and café establishments as well as a grand event finale. This paper summarises the primary and secondary research that form the foundation of the key campaign strategies. From the creative design conception to the execution of the campaign, this report takes into account the campaign’s tactical effectiveness through key evaluative measures. These include a pre-campaign survey, extensive in-depth interviews, and feedback from members of the public. The report also provides future recommendations for the continuation of similar reading initiatives in the future. For further reference, detailed appendices with specific graphs, tables and design details have been included.